Frequency Of Anxiety And Depression Among Sheikh Zayed Medical Students COVID-19 Post-Pandemic - Hussain, Ayesha; Masood, Rabiya; Qadeer, Sanober (Biological and Clinical Sciences Research Journal, 2025)
Anxiety and depression are highly prevalent among medical students worldwide, often exacerbated by academic stress, financial burdens, and lack of mental health resources. In Pakistan, where mental health awareness remains limited, the COVID-19 pandemic has further increased psychological distress among medical students. This study aims to evaluate the prevalence of anxiety and depression among medical students at Sheikh Zayed Medical College, Rahim Yar Khan, in the post-pandemic period and identify key risk factors contributing to these conditions. Objective: To determine the prevalence of anxiety and depression among 4th and 5th-year MBBS students and assess its association with gender, socioeconomic status, living conditions, and COVID-19-related experiences. Methods: A cross-sectional analytical study was conducted over six months at Sheikh Zayed Medical College, Rahim Yar Khan. A total of 145 medical students were enrolled using a stratified random sampling technique. Anxiety and depression were assessed using the Hospital Anxiety and Depression Scale (HADS), with a cutoff score of >10 indicating clinical significance. Data were collected via self-administered structured questionnaires and analyzed using SPSS version 26. Chi-square and independent t-tests were applied to determine statistical significance, with p ≤ 0.05 considered significant. Results: The overall prevalence of anxiety and depression was 55.8%. Female students exhibited significantly higher rates (63.3%) than male students (44.5%, p = 0.03). Anxiety and depression were more prevalent in students from low-income backgrounds (62.2%, p = 0.002) and hostel residents (62.7%, p = 0.04). Students with a history of a family member being affected by COVID-19 had a significantly higher prevalence (65.7%, p = 0.001), while those who lost a family member due to COVID-19 reported the highest rates (72.3%, p < 0.001). Conclusion: This study highlights the high burden of anxiety and depression among medical students in Pakistan, with socioeconomic factors, gender, living conditions, and COVID-19 exposure playing significant roles. Given the persistent psychological impact of the pandemic, targeted mental health interventions, financial support mechanisms, and counselling programs should be implemented in medical institutions. Future research should focus on longitudinal studies to assess mental health trends and intervention-based approaches to mitigate anxiety and depression among medical students.